Modular Framework for Constructing IoT-Server AKE in Post-Quantum Setting - Bowen Liu; Qiang Tang; Jianying Zhou (IEEE Access, 2022)
Authenticated key exchange (AKE) allows two parties to authenticate each other and establish a secret session key to build a secure channel, and it has been well studied in the literature. With the approaching of quantum computers, designing post-quantum secure AKE schemes becomes an urgent task. Today, several KE schemes have been proposed while only a small number of AKE schemes exist. Very few of them have considered resource-constrained participants like IoT devices. In this paper, assuming a typical client-server setting where the client is an IoT device, we propose a modular framework that converts any post-quantum secure KE scheme into a post-quantum secure AKE scheme. Equipped with two authentication factors, the resulted AKE scheme provides a number of security guarantees including Perfect forward secrecy (PFS), Key compromise impersonation (KCI) resilience and Server compromise impersonation (SCI) resilience. We further instantiate the framework by selecting the most efficient KE scheme, namely NewHope Compact, and implement the scheme with some optimisation techniques and conduct relevant analysis and comparisons. In a nutshell, the computational time of the server side is 1.11 ms on a PC and 6.22 ms of the IoT device simulated on Raspberry Pi 3B+, and it seems to be efficient enough for most IoT application scenarios.